Transnational Carding Crime Analysis Is Reviewed From International Criminal Law - Deardo Pieter Saragih; Astiya Putri Agussriani; Dera Andika S; Kevin Cesario Valentino Simanjuntak; Ganis Raditya Prabaswara (Jurnal Hukum dan HAM Wara Sains, 2022)
This article aims to find out transnational crimes of hacking-carding against human security, which in this case discusses examples of cases that have occurred, knows the factors that cause cyber fraud in terms of fraud triangle theory, knows about the modes commonly used by perpetrators , knowing about the juridical law that applies in this matter, and the impact and solution in this case. Technological advances in this developing era provide convenience but also provide opportunities for irresponsible people to commit crimes. Various kinds of crimes exist in cyberspace, one of which is credit card fraud. The case of credit card fraud is a case that is quite dangerous because this case has difficulty disclosing the perpetrators who did it, making this case more widespread and causing unrest in the community. This case also has the potential to disrupt human security and the security of the country that is the victim. One example of the case in September 2011 with the perpetrator using the data theft mode from credit card owners at shopping centers and gas stations which resulted in a nominal value of 81 billion.